DIGNITY OF THE DECEASED AND INTERVENTION. A CONCEPTUAL ANA LYSIS AND BASIS FOR ETHICA L REFLECTION - JEANNEROD, M.; GOFFETTE, J.; FANTON, L. (MEDECINE LEGALE DROIT MEDICAL, 2025)
For their status as a human being to be recognized and their ontological dignity to be respected, the deceased must be accorded a farewell ritual. During the period intervening before this ritual can be conducted, the “body” may undergo certain medical interventions: organ harvesting, body donation, autopsy, etc. This may lead to the inherent uniqueness of the individual being neglected. There is a serious danger of the deceased person being treated as a “thing”. The dead body is vulnerable and needs to be protected. It is therefore essential to define good practices based on the consideration that is to be accorded. This entails recognizing the specific value of each dead person, respecting their free will and last wishes so far as possible. Any extraneous physical degradation must be excluded. This extra effort required of those who deal with death as part of their work is neither straightforward nor instinctive. To achieve due consideration for the deceased in medical practice, the professionals concerned require accompaniment and support. If they themselves are given the requisite care and attention and a suitable working environment, they will be in a position to respect their fellow human in death and to “do no harm”.